(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper deals with the reviewfor existing work done in green computing &DevOps process. The paper mayhelp in abigger landscape of entire software development process models to analyze and implement green computing processes.Green computing inspires people to create software or infrastructure which is planet friendly and emit very less carbon compare to existing technology.These days DevOps is the very common process adopted within software development life cycle to produce the automated infrastructure, to automate the code promotion from non-production to production environments. Agile delivery model helps to deliver the expected client deliverables in terms of smaller release cycle to production so rather than waiting for entire product to get ready and reviewed late in stage the smaller chunks of feature gets verified early and deployed to production following all quality checks and process controls in place. This paper reviews the existing literatures available online to find the scope for the green computing-basedDevOps process in the software development life cycle.